Per una nuova cura dell'abitare - Acciai, Serena; Buonanno, Daniela; Di Palma, Bruna; Orfeo, Camillo (TeA/Teaching Architecture, 2022)
The publication collects the results of the four Laboratories of Architectural and Urban Design and Interior Architecture of the 5UE Master's Degree Course in Architecture of the DiARC of the Department of Architecture of the University of Naples "Federico II", which took place during the academic year 2020/2021. The exercises conducted by the students are located in the Vallone San Rocco area, falling within an urban area of PUA, and aimed at the care of the domestic and urban space through the experimentation of new forms of collective living, and particular attention to integration. cultural, social and generational. The theme of the living space was declined through the elaboration of different project scales: from the private internal space to the semi-public external space, ending with the collective open space, including agricultural and productive ones. The volume is completed by numerous essays by lecturers from the Department of Architecture, architects and experts demonstrating the transversal and central nature of the topic dealt with in the context of contemporary architectural research.